Pengaruh Posisi Kredit dan Dana Pihak Ketiga Terhadap Laba Bank dengan Non Performing Loan Sebagai Pemediasi: (Studi Kasus Pada Bank Perkreditan Rakyat di Lumajang) - BUDIWATI, HESTI (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2019)
This study aims to examine the effect of credit position and third party funds on bank profits both partially and simultaneously. The next goal is also to find out whether non-performing loans can be a mediator between the influence of credit positions and third party funds on bank profits. The research was conducted at the rural Bank in Lumajang consisting of 6 (six) banks. The analytical technique used is path analysis by testing the first substructure and the second substructure. Samples in the form of quarterly reports as many as 6 periods from 2015 to 2017, so the number of samples is 36 quarterly reports. The results of the study state that the credit position has a significant effect on non-performing loans, third party funds have no significant effect on non-performing loans, simultaneously the position of credit and third party funds have a significant effect on non-performing loans. The next result is the position of credit, third party funds, and non-performing loans does not have a significant effect on bank profits, but simultaneously all three have a significant effect on bank profits. Non-performing loans apparently also cannot be a mediator of the influence of credit positions and third party funds on bank profits. Future research is expected to examine other variables that influence bank profits